A three-dimensional numerical investigation of trapezoid baffles effect on non-isothermal reactant transport and cell net power in a PEMFC. (1st April 2015) - Perng, Shiang-Wuu; Wu, Horng-Wen
Highlights: We study how angle and height of trapezoid baffle affect PEMFC net power. The jet-type, trapping, and blockage effects augment non-isothermal transport in flow channel. Greater angles and heights of trapezoid baffles provide more reactant to the catalyst layer. Baffles of 1.5 mm and 90° fully block flow channel to show bad heat transfer and large pressure drop. Maximum enhancement of cell net power is 90% with baffles of 60° angle and 1.125 mm height. Abstract: The present study performed a three-dimensional numerical simulation to observe how trapezoid baffles affect non-isothermal reactant transports and cell net power in the proton exchange membrane fuel cell (PEMFC) by the SIMPLE-C method. The geometric parameters of trapezoid baffles installed in the gas channel employed in this study include the angle and height with the same gas diffusion and catalyst layers to realize the cell net power considering the effect of liquid water formation on the fluid flow field. The cell net power is adopted to evaluate the real enhancement of cell performance due to the additional pumping power induced by the pressure loss through the PEMFC. The results illustrated that compared with traditional gas channel without baffles, the novel gas channel with trapezoid baffles, whose angle is 60° and height is 1.125 mm, enhances the cell net power best by approximately 90% among all trapezoid baffle designs.